An In Vivo Validation of the Application of Acoustic Radiation Force to Enhance the Diagnostic Utility of Molecular Imaging Using 3D Ultrasound - Gessner, Ryan C. (2012)
For over a decade, the application of acoustic radiation force (ARF) has been proposed as a mechanism to increase ultrasonic molecular imaging (MI) sensitivity in vivo. Presented herein is the first noninvasive in vivo validation of ARF-enhanced MI with an unmodified clinical system. First, an in vitro optical-acoustical setup was used to optimize system parameters and ensure sufficient microbubble translation when exposed to ARF. 3D ARF-enhanced MI was then performed on 7 rat fibrosarcoma tumors using microbubbles targeted to α(v)β(3) and non-targeted microbubbles. Low-amplitude (< 25 kPa) 3D ARF pulse sequences were tested and compared to passive targeting studies in the same animal. Our results demonstrate that a 78% increase in image intensity from targeted microbubbles can be achieved when using ARF relative to the passive targeting studies. Furthermore, ARF did not significantly increase image contrast when applied to non-targeted agents, suggesting that ARF did not increase non-specific adhesion.